Pruritic Urticarial Papules and Plaques of Pregnancy (PUPPP) in Jakarta, Indonesia: A Comprehensive Assessment of Clinical Features, Risk Factors, and Management Outcomes - Rini Kuswohadi Pramono; Felicia Sari; Muhammad Yusuf; Nadia Khoirina (Sriwijaya Journal of Obstetrics and Gynecology, 2025)
Introduction: Pruritic urticarial papules and plaques of pregnancy (PUPPP), also known as polymorphic eruption of pregnancy (PEP), is a common, self-limiting dermatosis of pregnancy. However, its specific characteristics and management outcomes in Indonesia, a diverse and populous nation, remain understudied. This study aimed to comprehensively assess the clinical features, risk factors, and management outcomes of PUPPP in an Indonesian population. Methods: A retrospective cohort study was conducted at Private Hospital in Jakarta, Indonesia, between January 2019 and December 2023. Medical records of pregnant women diagnosed with PUPPP were reviewed. Data collected included demographics, gestational age at onset, clinical presentation (lesion morphology, distribution, pruritus severity), associated symptoms, parity, pre-pregnancy BMI, weight gain during pregnancy, smoking history, presence of comorbidities, treatment modalities, and treatment outcomes (symptom resolution time, recurrence). Statistical analysis was performed using SPSS version 28. Results: A total of 285 pregnant women were included in the study. The mean age was 29.5 years (SD ± 4.8). The majority (72.3%) were primigravida. Onset was most common in the third trimester (88.4%). The most frequent presenting symptom was severe pruritus (94.7%), followed by erythematous papules (98.2%) and urticarial plaques (91.6%). Lesions predominantly affected the abdomen (96.5%), particularly the striae distensae (89.1%), with frequent involvement of the thighs (75.4%) and buttocks (62.1%). Higher pre-pregnancy BMI (p=0.012) and excessive gestational weight gain (p=0.003) were significantly associated with PUPPP development. Topical corticosteroids (85.6%) were the most commonly used treatment, followed by oral antihistamines (68.4%). Symptom resolution occurred within a mean of 10.2 days (SD ± 3.5) after treatment initiation. Recurrence was observed in 8.4% of cases. Conclusion: PUPPP in Indonesian women predominantly affects primigravida in the third trimester, presenting with severe pruritus and characteristic lesions on the abdomen, thighs, and buttocks. Higher pre-pregnancy BMI and excessive gestational weight gain appear to be significant risk factors. Topical corticosteroids and oral antihistamines are effective in achieving symptom resolution. These findings highlight the need for increased awareness and appropriate management of PUPPP in Indonesia.